COP21 Africa pavilion: Scaling up innovative approaches to climate-smart agriculture in Africa - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
The objective of the session was to help inform the UNFCCC discussions and outcomes at COP21 by sharing information about specific scalable climate-smart solutions that can help millions of small-holder farmers in Africa, in several areas including adaptation, mitigation and food security. Photos: V. Atakos (CCAFS).